Current management of vaginal dryness - T.V. Tazina; A.V. Knyazeva; T.V. Bebneva (LCC «Medicine-Inform», 2021)
T.V. Tazina1, A.V. Knyazeva2, T.V. Bebneva3,4 1Ryazan State Medical University, Ryazan, Russian Federation 2Regional Clinical Hospital, Ryazan, Russian Federation 3Russian University of Peoples' Friendship, Moscow, Russian Federation 4National Medical Research Center of Endocrinology, Moscow, Russian Federation The proportion of women of perimenopausal and postmenopausal age increases every year. Hormonal changes which are typical for these women are characterized by hypoestrogenism and a great diversity of clinical signs, e.g., vaginal dryness, irritation, itching, pain, burning, dyspareunia, and frequent urination. These symptoms occur at any age but are more common in postmenopausal women. Genitourinary syndrome of menopause (GSM) significantly reduces the quality of life of postmenopausal women. Among GSM presentations, vulvovaginal atrophy affects only vulvar and vaginal mucosa. Managing vulvovaginal atrophy in women of various ages is an important issue of gynecological practice. This paper describes current approaches to the treatment for vulvovaginal atrophy in women of various ages with a special focus on the association between vaginal dryness and the reduction of both general and sexual quality of life. In particular, non-hormonal topical medications are discussed. Knowing current (including international) approaches to address vaginal dryness are important for obstetrical gynecological practice. Keywords: genitourinary syndrome of menopause, vulvovaginal atrophy, lubricants, vaginal moisturizers. For citation: Tazina T.V., Knyazeva A.V., Bebneva T.V. Current management of vaginal dryness. Russian Journal of Woman and Child Health. 2021;4(3):250-253 (in Russ.). DOI: 10.32364/2618-8430-2021-4-3-250-253.